Kerjasama Bilateral Indonesia-Jepang Melalui Program The Japan Foundation - Ulan Purnamasari; Aulia, Yuni; Marsella Marsella (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines bilateral cooperation between Indonesia and Japan which is realized through The Japan Foundation program, with an emphasis on cultural diplomacy as a soft power approach. Using descriptive methods and qualitative analysis of secondary data, this study reviews the contribution of The Japan Foundation in strengthening the relationship between the two countries in the cultural, educational, and economic sectors. The findings suggest that activities such as Japanese language learning, cultural festivals, and art exchanges play an important role in building cross-cultural understanding. Activities such as Ennichisai in Jakarta, cultural collaboration between Yogyakarta and Kyoto, and community empowerment initiatives in Bandung are proof of the success of this approach. Despite the disparity in cultural influence, Japanese cultural diplomacy has proven to be able to create a harmonious and mutually beneficial relationship for both parties.